AvaliaÃÃo formativa como regulaÃÃo da aprendizagem: desafios para a prÃxis no ensino mÃdio da rede pÃblica estadual de Fortaleza - uma anÃlise fenomenolÃgica - Sandra Maria Coelho de Oliveira (2015)
This research had as general main to investigate what the impediments and effective possibilities of formative assessment as regulating the process of learning in teaching practice of high school teachers of public school of Fortaleza, in order to contribute to its use as an element of learning promotion. The assessment, more than a technical discussion, involves a political debate about their educational purposes which often present distorted and misleading. The study was qualitative approach, having the phenomenological-hermeneutical method as a research option and data analysis, with emphasis on Heidegger's philosophy. According to Heidegger, phenomenology is to come from yourself what to manifest. So this assertion legitimizes the need to seek with teachers the essential elements to understand an assessment practice which allows their subjectivities, interests and knowledge of reality. The application of this method in the analysis of oral manifestations of the subjects intends to think the daily life of being a teacher, as your way of doing should be taken at unveiling, building qualitative contributions to the study. The research was conducted in six schools randomly selected. The subjects were 24 high school teachers who worked in four different areas of the curriculum and who met these criteria: to be effective teacher of the state system and act in teaching at least three years. The instruments and data collection techniques were questionnaire, the semi-structured interview, sensitive listening and participant observation in the classroom. The results indicated the coexistence of traditional assessment practices and practices with formative assessment features which rehearse a new assessment movement in daily school life, with more emphasis on first. The teachers, based on their experiential knowledge, create their own strategies, called phenomenologically as authentic assessment to evaluate of a continuous way. However, the various obstacles present in this context (the lack of teacher training in assessment, bad structural conditions, the pressure of external evaluations) act as impediment effective elements to formative assessment. The intended changes should be doubly qualified, in terms of training and material conditions, otherwise restricted to a technical improvement of immediative orientation, pragmatic and decontextualized. Thereby, it expects to raise reflections about assessment applied by teachers, in order to value formative function. The way to change in assessment practices requires the adopting public policies come to teacher training on assessment at institutional level of educational departments. Thus, we suggest to joint a public system of teacher training about assessment through courses. On initial formation level, the data suggest the need to include learning assessment as compulsory subject. Moreover, external assessments need to be more understood as examinations with specific functions which differ from daily school assessment, should raise discussions about power on curriculum and evaluative direction of schools. It also should prioritize more investiments on physical and pedagogical structures of schools. Ending, the conclusions of this study indicate some starting points to effective assessment process increasingly back to serve the learning.